The effect of palm oil fuel ash (POFA) and polyvinyl alcohol (PVA) on the physico‑mechanical, thermal and morphological properties of hybrid bio‑composites - Md. Rezaur, Rahman; Sinin, Hamdan; Elammaran, Jayamani; Akshay, Kakar; Muhammad Khusairy, Bakri; Fahmi Asyadi, Md Yusof (Springer Nature, 2020)
This study focuses on the effects of palm oil fuel ash (POFA) and polyvinyl alcohol (PVA) on the physico-mechanical, thermal and morphological properties of kenaf-/ jute-reinforced polyvinyl alcohol (PVA)/polyethylene (PE) hybrid bio-composites. The fibers were dried in an oven and mixed with PE and PVA at different fiber loadings, respectively (5 wt%, 10 wt%, 15 wt% and 20 wt%). The samples were prepared and tested according to ASTM standards. The scanning electron microscope shows that PVA reduces the agglomeration and increases the bonding between fiber and matrix. Jute/kenaf—PE/PVA composites (JKPEPVAC), show a higher tensile strength and Young’s modulus compared to jute/kenaf—PE composites (JKPEC), and jute/kenaf—PE/POFA composites (JKPEPOFAC). The composites have better compatibility between fiber, matrix and the PVA composite, which shows desirable properties and performances. TGA and DSC analysis confirms that the JKPEPOFAC has a higher thermal decomposition and activation energy and more thermal stability than JKPEC and JKPEPVAC.